Penerapan Strategi Marketing Communication pada PT PLN (Persero) - Meilyana; Faerrosa, Lady (Insan Kreasi Media, 2024)
Marketing communication strategies are a very important part of a company effort to convey valuable messages to consumers. This also applies to PT PLN (Persero) Induk Wilayah Nusa Tenggara Barat (PT PLN UIW NTB). Therefore, this service activity aims to help PT PLN UIW NTB implement various marketing communication strategies. The method of implementing this activity starts from the preparation, planning, preparation, implementation and evaluation stages. Some of the core activities carried out are the preparation of the PLN UIW NTB DimSum Podcast, creating PLN Mobile marketing content videos, monitoring news releases and media evidence of PT PLN UIW NTB. This entire series of activities was completed within one month. The results of this activity are the holding of podcast activities and positive news releases to help maintain the reputation of PT PLN UIW NTB. Through this activity, it is hoped that the company can continue to improve innovative marketing communication strategies and convey messages well and according to customers' objectives.